Development and optimization of geopolymer adsorbent for water treatment: Application of mixture design approach. (15th July 2023) - Aouan, Badr; Alehyen, Saliha; Fadil, Mouhcine; El Alouani, Marouane; Saufi, Hamid; El Herradi, El Hassania; El Makhoukhi, Fadoua; Taibi, M'hamed
Abstract: The current paper refers to the study of a new approach to optimizing the adsorptive properties of geopolymers by varying the aluminosilicate precursors from kaolin (K), metakaolin (MK), and coal fly ash (CFA) as internal synthesis factors. The simplex-augmented-centroid mixture design was applied to identify the optimal formulation from the three aluminosilicate precursors to develop a geopolymer (GP) with a distinctive structure that positively affects its dye adsorption efficiency. The variously formulated GP samples were tested for the removal of both methylene blue (MB-dye) and crystal violet dye (CV-dye) from an aqueous solution. The mathematical-statistical analysis of the experimental readings suggested that the generated special cubic models were significant, and thus the chosen approach was adequate for determining the optimum blending proportion. The optimization tools indicated that the optimal mixture from the three aluminosilicate precursors for developing a GP with high adsorption efficiency was 58% MK, 42% K, and 0% CFA. The optimized geopolymer (GPO ) was synthesized and then analyzed using a variety of physicochemical techniques, which revealed the presence of an amorphous N-A-S-H gel-rich porous structure as an influencing property on the geopolymer's organic dye adsorption efficiency. The dependence of the adsorption mechanism of both MB-dye and CV-dye by GPO on the adsorbent dosage, contact time, initial dye concentration, temperature, and solution pH was evaluated. The isothermic and kinetic experimental readings for MB and CV-dyes adsorption by GPO were well fitted to the pseudo-second-order and Freundlich models, with an exothermic, favorable, and spontaneous adsorption reaction thermodynamically. The experimental studies in the lab scale on GPO produce comparable results. From these results, it has been concluded that the accuracy and feasibility of the mixture design simulation succeeded in optimizing and developing a geopolymeric sorbent material with great potential as an excellent economical agent for removing cationic dyes from aqueous media. This point represents an added value compared to traditional non-optimized geopolymer absorbents. Besides, this geopolymer material represents a significant application possibility for water treatment and remediation of hazardous dye pollutants. Highlights: The geopolymer adsorbent was optimized using a mixture design methodology. The optimized geopolymer has been developed using a mixture of kaolin (58%) and metakaolin (42%). The optimized geopolymer showed maximum adsorption capacities of 63.79 and 73.00 mg/g for the MB and CV dyes, respectively. The adsorption mechanism fits well with the Langmuir isothermal and pseudo-second-order kinetic models. The optimized geopolymer adsorbent represents a relatively low synthesis cost.